India's communal constitution law, religion, and the making of a people - John, Mathew (Cambridge Cambridge University Press, 2023)
The book shows how the Indian Constitution identifies the Indian people in colonial and communal terms.
Description based on publisher supplied metadata and other sources
Keywords: Constitutional law-India; Communalism-India; Religion and law-India; Caste-India; Minorities-Legal status, laws, etc.-India; Equality before the law-India; India-Social conditions; India-Politics and government